Fine spectra of tridiagonal Toeplitz matrices - Altun, M.; Bilgiç, H. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 514.74 The fine spectra of $n$-banded triangular Toeplitz matrices and $(2n+1)$-banded symmetric Toeplitz matrices were computedin ( M. Altun, Appl. Math. and Comput. – 2011. – 217. – P. 8044 – 8051) and ( M. Altun, Abstr. and Appl. Anal. – 2012. –Article ID 932785). As a continuation of these results, we compute the fine spectra of tridiagonal Toeplitz matrices. Thesematrices are, in general, not triangular and not symmetric.